TINGKAT DEPRESI MASYARAKAT PADA MASA PANDEMI COVID-19 DI DUSUN PUGERAN DESA KALIBOTO KECAMATAN TAROKAN KABUPATEN KEDIRI - Ariani Sulistyorini; Nia Meyga Pratiwi (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
The Covid-19 virus has been declared a pandemic since mid-March 2020. The increasing number of Covid-19 cases has caused public concern, causing an increase in psychological distress, one of which is depression, which is a mental disorder in someone with declining feelings such as feeling sad, gloomy, and feeling depressed. The purpose of the study was to determine the level of depression in the community during the Covid-19 pandemic. The research design is Descriptive and cross-sectional, the research population of the whole society in Pugeran hamlet has as many as 572 respondents with a sample of 57 respondents using the purposive sampling technique. The research was carried out on 1-28 February 2022, the research variables were the level of depression in the community during the Covid-19 pandemic, the research instrument was the DASS 42 questionnaire (Depression, Anxiety and Distress Syndrome 42), the data that had been collected was then analyzed using a frequency distribution table. The results of the study were 57 respondents, almost half of them, namely 16 respondents (28%) did not experience depression (normal), most of them were 29 respondents (51%) had mild depression, a small part, namely 11 respondents (19%) moderate depression, a small part, namely 1 respondent. (2%) severe depression and none of the respondents experienced severe depression. This is caused by factors of age, gender, occupation, marital status, experience suffering, information, and sources of information about Covid-19. The results of the study are expected to be additional material for educational institutions in providing information about the level of depression in the community during the Covid-19 pandemic. People can control their psychological condition by making good lifestyle changes such as always thinking positively and being realistic so that people's depression does not increase. Health workers are expected to regularly provide mental health counseling to the community